MEMBANGUN KARAKTER KEWIRAUSAHAAN PEREMPUAN PERSPEKTIF AL-QURâAN DALAM MENINGKATKAN PRODUKTIFITAS PEREKONOMIAN - Rosyad, Afthonur (Jurnal al Hikmah, 2017)
The Quran is the word of God which is the reference point of man. The Quran is a guide to man (hudan li-nas). As the word of Allah the Quran will always be dynamically reviewed according to time and place. One of the things that became a study in the Quran is women. Women in Islam have a strategic role in developing their abilities. Respect for women today is already proven by the participation of women in all aspects of life. Starting from the family environment to the state of the country even women have an important role, as the evidence in the field of social, economic, political, cultural, women play a role. Equality of position between men and women in this modern era is almost equal. However, there are still many irregularities that occur due to lack of womens awareness and lack of attention to the role of women. Under such conditions it is imperative to build womens mental readiness within the scope of entrepreneurship. It is intended to expand the role of women themselves as one who has the optimal potential to be developed.